Surface Morphology of Basalt Columns at Svartifoss, VatnajökulsÞjóðgarður, Southern Iceland. (3rd December 2013) - Tanner, Lawrence H.
Abstract : A spectacular example of columnar-jointed basalt occurs at Svartifoss in the Vatnajökull National Park of southern Iceland. The columns are notable for a variety of features on the vertical joint surfaces and the horizontal parting surfaces. The jointed surfaces of the columns display horizontal striations at a spacing of centimeters to decimeters. The individual striations exhibit crescentic hackles with a plumose pattern, the orientation of which varies between adjacent striations. Also present are gently dipping, millimeter-scale laminations not previously described. Horizontal parting surfaces of the columns display a circular ring that inscribes most of the diameter column. The ring features alternately positive or negative relief against the perimeter of the column and exhibits a radiating pattern of hackles originating at the center of the ring. Petrographic examination reveals that the basalt contains an interlocking network of plagioclase laths preferentially aligned perpendicular to the column axes. The circular features have been described previously and attributed to late-stage melt migration driven by a load-induced pressure gradient. The striations were formed from stepwise, downward propagation of the polygonal fracture system, and the plumose structures were formed from tensile stresses during fracture propagation. The small-scale laminations may result from preferential grain alignment of plagioclase laths.